2002
DOI: 10.1046/j.1526-0968.2002.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hemodiafiltration with Polymyxin‐B Immobilized Fiber Is Effective in Patients with Sepsis Syndrome and Acute Renal Failure

Abstract: The aim of this study was first, to evaluate the effects of continuous hemodiafiltration (CHDF) alone or combined with CHDF and polymyxin-B immobilized fiber (PMX) on survival rates of patients with sepsis and acute renal failure, and second, to evaluate the changes in plasma levels of inflammatory cytokines before and after treatment with CHDF and PMX and CHDF alone in these patients. Forty-eight patients with septic shock and acute renal failure were enrolled in this study. The survival rate of all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 36 publications
1
48
1
Order By: Relevance
“…PMX-DHP is an effective radical treatment for septic shock. However, although it was reported that PMX-DHP improved lung function in acute lung injury and acute respiratory distress syndrome, 12 and renal function in combination with CHDF in acute renal failure, 13 those effects were not observed in the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…PMX-DHP is an effective radical treatment for septic shock. However, although it was reported that PMX-DHP improved lung function in acute lung injury and acute respiratory distress syndrome, 12 and renal function in combination with CHDF in acute renal failure, 13 those effects were not observed in the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…Various new technologies, including plasma exchange, continuous hemofiltration, continuous hemodiafiltration, and PMX-DHP, have been reported to be useful methods for removal of these humoral mediators from blood, resulting in the improvement of prognosis [1,10,[23][24][25]. PMX-DHP was originally developed for selective adsorption of endotoxin in patients with Gram-negative bacterial infection [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of a number of other mediators have been reported after PMX. The list includes IL-6 [12,13,14], IL-10 [13,14], IL-18 [15], TNF-α [14,16], metalloproteinase-9 and tissue inhibitor of metalloproteinase-1 [7], plasminogen activator inhibitor-1 [14,16,17], neutrophil elastase [9,18], platelet factor-4 [15], β-thromboglobulin [15], soluble P selectin [15] and endogenous cannabinoids [15,19] such as anandamide. Several of these mediators cause lung injury, increase vascular permeability and worsen intrapulmonary shunting.…”
Section: Pmx In Acute Respiratory Failurementioning
confidence: 99%